P05.04 Antimicrobial susceptibilities of persons with gonorrhoea at multiple sites are accurately reflected by urogenital specimens. (13th September 2015) - Dixon, P; Van Der Pol, B; Swerdlow, J; Cammarata, S; Sun, E; Hook, EW
Abstract : Background: Surveillance for gonococcal (GC) antimicrobial resistance is focused on susceptibilities of urogenital GC isolates. The ability of surveillance programs utilising only urogenital specimens to detect resistance in communitites could theoretically be compromised if extragenital (i.e. pharyngeal or rectal) GC infectons were more often resistant. We evaluated how GC antimicrobial susceptibilities at extragenital sites varied when compared to contemporaneously isolated urogenital infections. Methods: We determined GC agar dilution MICs for ceftriaxone, cefixime, ciprofloxacin and azithromycin in isolates from 57 participants with multisite infections in a recent multicenter GC treatment trial. Results: Extragenital infections were more common among men with male partners (MSM – 23 [19%] of 118) and women (21 [18%] of 118), than men with female partners (MSW- 13 [8%] of 169) In this study all extragenital infections in MSWwere pharyngeal while pharyngeal isolates comprised about half of extragenital infections from MSM (12\[52%] of 23) and women (14[67%] of 21, respectively). MICs were meaningfully different (2 or more dilutions) between urogenital and extragenital sites in 9 (16%) of 57 persons (14[6%] of 228 comparisons) with multiple site infections. Ceftriaxone or cefixime MICs varied between urogenital and extragenital sites in just 2 participants while MICs for ciprofloxacin and azithromycin varied in 3 and 7 participants, respectively. Only urogenital isolates from women and MSM had significantly elevated MICs to azithromycin when patients with infections at multiple sites were compared to those with only urogenital infection. There was no consistent pattern to these differences; in 5 urogenital MICs were greater than extragenital sites while in the remaining 4 participants, extragenital MICs were greater than for urogenital sites. Conclusions: MICs for urogenital sites of infection most often reflect MICs of extragenital isolates in persons with multiple simultaneous sites of infection and are suitable for surveillance for antimicrobial resistance. Disclosure of interest: Funding for this study was provided by Melinta Therapeutics.